The impact of the mission statement of the political and moral guidance authority on the performance of its employees - Gaza Strip (Economic studies journal, 2023)
The study aimed to find out the impact of the message of the Political and Moral Guidance Authority on the performance of workers in the Gaza Strip, in four axes of the message of the authority, including (satisfaction of the target, the service provided, research and development, and employees). 164 employees, and the study sample was selected using the simple random sampling method, which amounted to (115) employees, and (95) questionnaires were retrieved, at a rate of (82.6%). The results of the study showed that the average degree of the commission’s mission axes was (73.2%), and the results also showed that the performance of the employees is high, but not in the expected manner, as it reached (76.7%). A statistically significant effect of the mission of the commission on the performance of the workers, as it showed that there are statistically significant differences between the mission of the commission and the performance of the workers attributed to the place of work in favor of the commission’s office, while there are no statistically significant differences between the mission of the commission and the performance of the workers due to (gender, age group, and educational qualification, years of service, and job title). The study recommended that more attention should be paid to taking feedback from the target groups about the activities in order to develop programs and activities.
Keywords: Mission statement; employee performance; political and moral guidance board; Gaza Strip